Voices of conflict : desegregating South African universities - Mabokela, Reitumetse Obakeng (Garland reference library of social science, 2000)
Examines how programs and structures at historically white universities have responded to the increasing enrollment of black students since the enactment of the Universities Amendment Act in 1983.